La ideología de los pequeños y medianos productores cafetaleros costarricenses (1900-1961) - Acuña O., Víctor Hugo (Revista de historia., 1987)
This article describes the ideology of small and medium coffee producers in Costa Rica. Their ideology offers an evolutionary and progressive view of social dynamics, and constantly emphasizes institutional and legal procedures as the means for regulation of social life. It is an ideology which praises peacefulness and social harmony. The Costa Rican coffee ideology is seen as persistent and very influential in the country´s intellectual history.